PROSEDUR AUDIT ATAS AKUN PIUTANG USAHA PADA PT ABC OLEH KAP JEPTHA NASIB & JUNIHOL - Mutiara Qalsum, (2021)
Audit procedures are procedures performed by the auditor to test the financial statements presented by the company's managemen. Accounts receivable is a loan of money given by a company to a party in need, and is one of the most important elements in the statement of financial position to ensure that the recording is appropriate and free from misstatement. Therefore, in carrying out audit procedures on accounts receivable, it is necessary to design and conduct audit programs properly and correctly. Audit procedures for accounts receivable account conducted by KAP Jeptha Nasib & Junihol is a company engaged in the construction sector. The implementation of the test starts from the audit acceptance stage, the audit planning stage, the audit testing stage, and the audit reporting stage. It can be concluded that PT ABC's accounts receivable during 2020 have been presented fairly without exception.